IMPLEMENTASI PROGRAM SOFTWARE AKUNTANSI ACCURATE ONLINE UNTUK GEREJA - Rimbun C.D Sidabutar; Sri Ida Royani Simanjuntak (Jurnal Abdimas Bina Bangsa, 2023)
HKBP District VII Samosir Church is a non-profit organization that is required to present financial reports in accordance with ISAK 35 which include statements of financial position, reports of comprehensive income, reports of changes in net assets, reports of cash flows, and notes to financial statements. Then, the enactment of the HKBP Church Finance Centralization policy, since January 2023, adds to the importance of preparing church financial reports to support the independence of each church in managing its finances. The obstacle that is generally faced by the HKBP Church is the limited ability of human resources to prepare financial reports because not all church officials, in this case the Treasurer or Secretary to the Treasurer of the Church have an accounting education background. For this reason, tools are needed to facilitate the preparation of financial reports. The Digital Accurate Accounting Software program is an accounting program that can present financial reports faster and more easily accessed anywhere. The introduction and training of the Digital Accurate AccountingSoftware program at the HKBP District VII Samosir Church is carried out through Community Service with the hope that the Church Treasurer or Secretary Treasurer as well as the Resort Pastor understand and find it easy to prepare church financial reports. The result of this community service activity is that church officials are able to operate features in the Digital Accurate accounting Software program in recording church transactions and presenting financial reports